(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Our research explores several entropy measurements for both EE (Exponentiated Exponential) and TEE (Truncated Exponentiated Exponential) lifetime models that scientists commonly use in their reliability projects. Our research develops various measures of entropy such as Shannon and Rényi to precisely measure uncertainty and unpredictability within these statistical distributions. The research analyzes entropy behavior across changing distribution parameters and contrasts EE with TEE results. The results show what exactly connects distribution parameters to their entropy measurements and shows why each distribution is special. This study enhances statistical and information theoretical methods for general use by showing all known uncertainty characteristics of EE and TEE distributions.